The value of a by-election - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2012)
Assistant Professor of Law Eugene K B Tan argues that if Parliament eventually determines that the Hougang seat has been vacated with the expulsion of Mr Yaw Shin Leong from the Workers' Party (WP), the spotlight will shift to Prime Minister Lee Hsien Loong who will advise the President whether to issue an election writ stipulating when a by-election is to be held.